Algorithms of Determining the Optimal Structure of a Telecommunication`S Power Supply System Based on Morphological Synthesis - Qodirov, Fazliddin; Qodirova, Sabrina (International Journal on Human-Computing Studies, 2023)
It is necessary to develop design principles and methods based on morphological synthesis and analysis of technical solutions to solve the problem of optimal design of power supply systems for a telecommunications power supply system. The essence of the morphological method is that it is necessary to determine several morphological features that are important for the problem being solved, and to make all possible combinations of these features. Its advantage over other methods is that it is possible to analyze the functional characteristics of the power supply system, its actions in a dynamic mode under the influence of changes in the network, load and change the mode of the operation. This article studys the optimal structure of the telecommunications power supply system.